UI/UX Design Web-Based Online Course as a Place for Hard Skill Improvement: Kursus Online Berbasis Web Desain UI/UX sebagai Tempat Peningkatan Keterampilan Keras - Muhammad Taufik Azis; Mohamad Jajuli (SYSTEMATICS, 2022)
With intense job competition, skills are needed that can give them an advantage over other candidates. Skills greatly affect what kind of work you want. When choosing a job, the important thing to have is hard skills. Hard skills can be learned by anyone. One of the places to improve hard skills is by using an online course platform. Currently, there are lots of online courses to improve skills, but many users are still confused about choosing the right course. The category of courses that are only divided according to academic knowledge and the absence of difficulty levels in the courses also make users confused about choosing a course. Therefore, from this problem an idea and solution was made in the form of an online course prototype called Skilverse. In this research, the method used is a Design Thinking approach which has 5 stages, namely empathize, define, ideate, prototype, and test. The prototype that has been made is also tested on respondents to validate whether the solution that has been made can solve user problems. The test method uses SEQ, namely by giving a task to the respondent by giving a Likert scale from 1 to 7.